Resistencia, cambio y adaptación en las universidades argentinas: problemas conceptuales y tendencias emergentes en el gobierno y la gestión académica - Suasnábar, Claudio (2001)
This article aims to contribute to the theoretical and methodological debate on the most suitable conceptual frameworks for studying the problems of government and management in Argentinian universities. The paper also constitutes a first test of the instruments presented therein. Tensions generated by state policies on academic management are also analysed. The article considers that the emergence of a double line of manegement and condut of the institution of new actors in Argentinian universities constitute the two phenomena which dispute the role historically attributed to academic councils. These tensions, which underlie processes of institutional change the, are the expression of conflicts between new forms of management and the model of co-government that established the Argentinian University Reform of 1918.